UJI TEKNIS ALAT PENYULING DAUN CENGKEH METODE UAP SKALA KECIL - Diana Marice Jitmau; Dedie Tooy; Ireine A. Longdong (Universitas Sam Ratulangi, 2023)
ABSTRACT Clove plants contain essential oils found in flowers (10-20%), stalks (5-10%), leaves (1-4%). In many places, the clove leaf is not used optimally. This can be seen in clove plantations where the fallen leaves are left alone in the garden. Clove leaf processing equipment into essential oil is relatively limited, therefore a clove leaf distiller was designed the steam method. The yield and performance of the tool need to be measured, to find out the performance of the tool design that has been made. For this reason, this study aims to conduct a technical test of the tool with variations in the volume of water that will be vaporized differently by measuring the temperature of the kettle and the time the first drop of condensate occurs, the volume of oil, the temperature of the condenser, the yield and the 2 color of the oil. This study used an experimental method by conducting 3 (three) experiments with different boiler water volumes, P1: 15 liters of water, P2: 35 liters of water, and P3: 45 liters of water with 3 (three) replications in each experiment. The research data are presented in the form of graphs and tables. The results showed that the higher the volume of boiler water, the longer the time the first droplet of condensate occurred. At a boiler water volume of 15 liters, the first droplet of condensate occurs at a boiler temperature of 82.56 °C and the time of the first droplet of condensate occurs at the 95th minute, while the volume of boiler water is 35 liters and 45 liters occurs the first droplet of condensate at a boiler temperature of 66.33 °C and 91.33 °C and the time of the first droplet of condensate in the 100 minute and 110 minute. The volume of clove essential oil produced is increasing at a volume of 45 liters of boiler water as much as 6 ml, while the volume of 35 liters of boiler water is 5.3 ml and the volume of boiler water is 15 liters as much as 3 ml. The condenser temperature produced in all three boiler water volume experiments was 10 °C. The highest amendment was found in the volume of boiler water of 45 liters, which was 0.848%, in the volume of boiler water of 35 liters, which was 0.646% and the volume of boiler water of 15 liters, which was 0.621%. The color of the resulting oil is dark brown. Keywords : Essential oil, Clove leaf, Technical test, Steam method